Biochemical responses to chilling injury in sweet potato after cold storage (Acta Scientiarum. Agronomy, 2023)
This study examined biochemical changes associated with chilling injury (CI) in sweet potato roots stored at low temperatures and reconditioned at ambient temperature. Sweet potato cultivars BRS Amélia and BRS Rubissol were stored at 6 or 13°C for 4 days at ambient temperature (“ambient reconditioning”: 21 ± 2°C). CI on the outer surface of the roots occurred earlier in BRS Amélia than in BRS Rubissol. The CI index on the inner surface of the BRS Amélia was higher when it was stored at 6°C for 40 + 4 days. BRS Amélia showed higher proline content and electrolyte leakage when stored at 6°C. Ascorbate peroxidase was induced by storage at 6°C for 30 + 4 days in BRS Amélia and from 40 + 4 days in BRS Rubissol. The malondialdehyde and phenolic compounds of BRS Rubissol increased during storage at 6°C. CI in both cultivars was associated with increased peroxidase and polyphenol oxidase activities. Storage of sweet potato cultivars at 6°C for 50 + 4 days caused severe damage to the roots. Cultivars BRS Amélia and BRS Rubissol showed similar symptoms of CI and can be characterized as being sensitive to low temperatures.